Retrospective evaluation of prehospital triage, presentation, interventions and outcome in paediatric drowning managed by a physician staffed helicopter emergency medical service. Issue 1 (December 2015) - Garner, Alan; Barker, Claire; Weatherall, Andrew
Abstract Background Drowning patients may benefit from the advanced airway management capabilities that can be provided by physician staffed helicopter emergency medical services. The aim of this study is to describe paediatric drowning patients treated by such a service examining tasking systems, initial physiology at the incident scene, survival and neurological outcome. Methods Retrospective analysis of paediatric drowning victims over a 5- year period. Case identification system, patient age, site of drowning, presence or absence of cardiac output, first Glasgow Coma Scale (GCS) score and interventions were collected from prehospital notes, and survival and neurological outcomes from hospital and rehabilitation notes. Results The P-HEMS direct case identification system operating in parallel with a central control system identified all severe drowning cases but 3 of 7 cases (43 %) were missed when the central control system operated in isolation. All severe drowning cases (22) identified for P-HEMS response were intubated and transported directly to a paediatric specialist centre. Intubation required adjuvant anaesthesia in 10 (45 %) cases. All children with GCS greater than eight on arrival of the P-HEMS survived neurologically intact. Seven of eight children with a GCS between four and seven survived without neurological impairment and all children with a GCS greater than three survived. Four of twelve asystolic children survived including one child who at 18 months post drowning is neurologically normal. All children who survived had return of spontaneous circulation prior to arrival in the emergency department. Conclusions P-HEMS played a significant role in the management of severe paediatric drowning in this case series. Requirement for P-HEMS only interventions were high and all identified cases were transferred directly to a paediatric specialist centre. Discontinuation of the P-HEMS direct case identication system that operated during the majority of the study period resulted in deterioration in system performance with some paediatric drowning cases subsequently not identified for P-HEMS response being transported to adult hospitals.